Serving the Patron Through Referral Lists: The Brooklyn Experience - Eriksen, Norman J.; Maas, Jan A. (Journal of interlibrary loan, document delivery & electronic reserve, 1997)
Describes referral lists created by the Education, Job and Computer Center at the Brooklyn Public Library to help patrons with employment, job training, or educational opportunities. Highlights include the creation process, distribution, use, and an appendix that includes referral list procedures. (Author/LRW)